Child work and schooling under trade liberalization in Indonesia - Krisztina Kis-Katos; Robert Sparrow (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2009)
We examine the effects of trade liberalization on child work and schooling in Indonesia. Our estimation strategy identifies geographical differences in the effects of trade policy through district and province level exposure to reduction in import tariff barriers. We use seven rounds (1993 to 2002) of the Indonesian annual national household survey (Susenas), and relate workforce participation and school enrolment of children aged 10-15 to geographic variation in relative tariff exposure. Our main findings show that increased exposure to trade liberalization is associated with a decrease in child work and an increase in enrolment among 10 to 15 year olds. The effects of tariff reductions are strongest for children from low skill backgrounds and in rural areas. However, a dynamic analysis suggests that these effects reflect the long term benefits of trade liberalization, through economic growth and subsequent income effects, while frictions and negative adjustment effects may occur in the short term.
Keywords: F14; F16; I21; J24; 330; child labor; schooling; trade liberalization